The activated carbon as anti-odour coated and pigment printed fabric / Tuan Sharifah Mas Eza Syed Mamat - Syed Mamat, Tuan Sharif Ah Mas Eza (2015)
In principle, textiles with anti-odour finishes are able to improve fabric quality by eliminating unpleasant odour making the wearers become more comfortable and confident with themselves. The present odour absorbers such as silver are very expensive. Therefore, the use of an alternative odour absorber like activated carbon is more affordable. In this study, activated carbon produced from coconut (CSAC) and oil palm shells (OPSAC) were applied in different percentages (5%, 10% and 15%) on polyester and cotton fabrics through coating and pigment printing techniques. The pigment printing was combine design and odour absorber on same piece of fabric. The coating technique was used as comparison for the effectiveness of odour absorber. These techniques are economic because using cheaper odour absorber i.e. activated carbon compared with commercial odour absorber i.e. Silver. Two types of odour measurements were conducted to evaluate the effectiveness of the anti-odour activated carbon which was through the Human Olfactory Tests and Machine Olfactory Tests using a device called Portable Electronic Nose 3 (PEN 3). Prior to the tests, the treated and control fabric samples were exposed to onion odour as substitution to body odour. The results showed that fabrics containing activated carbon were able to reduce odour that was picked up by the fabrics. The coated activated carbon fabrics gave better result than the printed activated carbon fabrics. The higher the concentration of activated carbons on the fabrics, the lower it generates odour intensity and odour annoyance, which also lower the odour of onion on the fabrics.